HUMAN RESOURCE-BASED ENTREPRENEURSHIP IN ERA OF INDUSTRIAL REVOLUTION 4.0 : A STUDY ON DIGITAL STARTUPS IN MEDAN - Muhammmad Isa Indrawan; Hasrul Azwar Hasibuan; Elfitra Desy Surya; Rahul Ardian Fikri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of the Industrial Revolution 4.0 has brought significant changes in the business world, especially in the digital startup sector. In this context, human resources (HR) are the key elements that determine the success of entrepreneurship. This study aims to analyze the role of human resources in encouraging the success of entrepreneurship in digital startups in Medan City. The approach used is quantitative descriptive with data collection through questionnaires distributed to digital startup actors. Data analysis was carried out using linear regression techniques to test the influence of human resource competencies on business success. The results show that human resource competencies that include innovation skills, mastery of digital technology, adaptive flexibility, and team collaboration have a significant influence on the success of startups. These findings confirm that in the era of the Industrial Revolution 4.0, strengthening the quality and capacity of human resources is a crucial strategy for the growth and sustainability of digital startups. This research provides practical contributions for business actors and local governments in building a digital entrepreneurship ecosystem based on the development of superior human resources.